2005
DOI: 10.1055/s-2005-858534
|View full text |Cite
|
Sign up to set email alerts
|

Karunkeltumor unklarer Dignität

Abstract: Tumors of the caruncle are very heterogenous because the caruncle contains tissues of the conjunctiva and the epidermis. Therefore to exclude a malignant process an excisional biopsy should always be performed even so in general tumors of the caruncle are benign. The most frequent tumors of the caruncle are papilloma, nevi, pyogenic granuloma, epithelial inclusion cyst and chronic inflammation. In only 4 % of the cases oncocytomas are found even the oncocytoma is considered to be a typical tumor of the caruncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In our study, patients with oncocytoma were generally older (≥ 55 years; median 70 years) which is in accordance with other studies [ 1 , 6 8 , 33 , 34 ]. Only Luthra et al reported a patient in his thirties with an oncocytoma [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, patients with oncocytoma were generally older (≥ 55 years; median 70 years) which is in accordance with other studies [ 1 , 6 8 , 33 , 34 ]. Only Luthra et al reported a patient in his thirties with an oncocytoma [ 7 ].…”
Section: Discussionsupporting
confidence: 92%